MANAJEMEN KURIKULUM BERBASIS TAUHID DAN IMPLEMENTASINYA PADA AKTIFITAS SISWA KELAS XII SMA LUQMAN AL-HAKIM PONDOK PESANTREN HIDAYATULLAH SURABAYA - Sulaiman Hasan (Studia Religia : Jurnal Pemikiran dan Pendidikan Islam, 2022)
This research discusses about how is the curriculum management based on tawheed at Luqman Al-Hakim Senior High School Surabaya; How is the implementation of the curriculum based on tawheed for Class XII students of SMA Luqman Al-Hakim Surabaya; How are the activities of Class XII students at Luqman Al-Hakim Senior High School Surabaya; and what are the obstacles and solutions in implementing the curriculum based on tawheed in class XII at Luqman Al-Hakim Senior High School Surabaya. The type of research is field research, with qualitative descriptive methods, data collection by interviewing managers, educators and education staff, observation, documentation of the Luqman AL-Hakim High School Surabaya. The data were analyzed qualitatively and managed in a descriptive form. The results of the research, first: Curriculum management based on Tawheed and its implementation is very effective at the Luqman Al-Hakim Senior High School Surabaya. Second : The curriculum structure of SMA Luqman AL-Hakim Surabaya is a paradigmatic curriculum which consists of three main components of educational material which also become distinctive characteristics, namely (1) the spiritual aspect, (2) the Aqliyah aspect and (3) the Jismiyah aspect, then the contents of the curriculum material consists of religious sciences, general sciences and skills. Third: The priority of implementation curriculum based on Tahweed in courtesy and science using the recitation, tazkiyyah, and ta'limah methods. Fourth: Implementation of the curriculum based on Tahweed appears in the character of Tawheed. Fifth: the obstacles: the frequent rotation of managers and lack of religious knowledge in new human resources, the slow implementation of the Tawheed character in boarding students due to contamination of new characters brought by full day students. Fifth: the solutions : Reduce the rotation of managers and priorities to recruitment of qualified human resources in the fields of expertise and religion, zoning of full-day students and boarding. Penelitian ini membahas tentang bagaimana manajemen kurikulum berbasis tauhid di SMA Luqman Al-Hakim Surabaya; bagaimana implementasi kurikulum berbasis tauhid pada siswa Kelas XII SMA Luqman Al-Hakim Surabaya.; bagaimana aktivitas siswa Kelas XII SMA Luqman Al-Hakim Surabaya; dan apa hambatan dan solusi dalam implementasi kurikulum berbasis tauhid di kelas XII SMA Luqman Al-Hakim Surabaya. Jenis penelitian adalah field research, dengan metode deskriptif kualitatif, pengumpulan data dengan wawancara terhadap pengelola, tenaga pendidik dan kependidikan, observasi, dokumentasi sekolah SMA Luqman AL-Hakim Surabaya. Data tersebut dianalisis secaara kualitatif dan dikelola dalam bentuk deskriptif. Hasil penelitian, pertama: Manajemen kurikulum berbasis tauhid dan implementasinya sangat evektif di Lembaga Pendidikan SMA Luqman Al-Hakim Surabaya. Kedua: Struktur kurikulum SMA Luqman AL-Hakim Surabaya adalah kurikulum paradigmatik yang terdiri dari tiga komponen materi pendidikan utama yang sekaligus menjadi karakteristik khas, yaitu (1) Aspek Ruhiyah, (2) Aspek Aqliyah dan (3) Aspek Jismiyah, maka isi materi kurikulumnya terdiri dari ilmu-ilmu agama, ilmu-ilmu umum dan keterampilan. Ketiga:Prioritas implementasi kurikulum berbasis tauhid pada adab dan ilmu dengan metode Tilawah, Tazkiyyah, Ta’limah. Keempat: Implementasi kurikulum berbasis tauhid tampak pada karakter tauhid Kelima: hambatannya: Seringnya rotasi Pengelola dan kurangnya pengetahuan agama pada SDM baru, lambannya implementasi karakter tauhid pada peserta didik boarding disebabkan kontaminasi karakter baru yang dibawa peserta didik full day. Kelima: Solusi Kurangi rotasi pengelola dan prioritas Rekrutmen SDM memumpuni di bidanng keahliannya dan agama, zonasi santri fulday dan boarding (berasrama).